COLLABORATIVE GOVERNANCE DALAM PENYELESAIAN BANJIR MELALUI PROGRAM DONASI SAREBU RUPIAH PER UMPI UNTUK SUNGAI CISALATRI DI KELURAHAN CIPADUNG KIDUL KECAMATAN PANYILEUKAN KOTA BANDUNG PROVINSI JAWA BARAT - Ridwan Trisno Setiawan Sadum (Ensiklopedia of Journal, 2022)
The Serebu Rupiah Per Umpi Donation Program for the Cisalatri River (Dona Sapitri) is a program of the Panyileukan District in facing the rainy season. Overcoming this incident, the sub-district has a community called Dona Sapitri (Donations of Serebu Rupiahs Per Umpi). This community was formed as a form of community mobilization. The Dona Sapitri community or donations for the Cisalatri river consists of 14 RW or about 17,000 residents of Cipadung Kidul. The goal is to make the river function properly. However, in the implementation of this program, it has not run as it should, there are still many obstacles that are felt so that the objectives of this program have not been achieved optimally. In this study, researchers used a descriptive method with an inductive approach. The results of this research are: (1) Overall, collaborative governance in flood resolution through the sarebu rupiah per umpi donation program for the Cisalatri River in Cipadung Kidul Village, Panyileukan District cannot be said to be successful. (2) There are three factors that support the Sarebu rupiah donation program for the Cisalatri River in Cipadung Kidul Village, Panyileukan District, namely: (a) Government support factors. (b) Fund support factor. (c) Community support factor. (3) The ideal model of collaborative governance in flood resolution through the Sarebu rupiah per umpi donation program for the Cisalatri River in Cipadung Kidul Village, Panyileukan District is: (a) Making an initial agreement, namely as a shared value. (b) Building leadership. (c) Building legitimacy. (d) Build trust. (e) Managing conflicts. (f) Planning.